Preconception micronutrient supplementation positively affects child development at 6 years of age: A randomized controlled trial in Vietnam - Nguyen, Phuong Hong; Young, Melissa F.; Khuong, Long; Duong, Thai Hong; Nguyen, Hoang Cong; Truong, Truong Viet; DiGirolamo, Ann; Martorell, Reynaldo; Ramakrishnan, Usha (American Society for Nutrition, 2020)
While there is growing evidence on the role of preconception nutrition for birth outcomes, very few studies have evaluated the effects of nutrition interventions during the preconception period on child development. This study evaluates the impact of preconception weekly multiple micronutrients (MM) or iron and folic acid (IFA) supplementation compared to FA alone on child growth and development at age 6–7y.